Hope - Lemons, Lakisha; Aitch, Jai; Johnson, LeMarc; Seretti, Timeca; Irving Films & Productions; Leomark Studios ([Houston, Texas] : Irving Films & Productions, 2016)
A young man hits rock bottom and nowhere to turn. With the loss of all hope, desire and motivation. He is slowly build back up through faith and trust in God. --
Originally released as a motion picture in 2016.
LeMarc Johnson, Timeca Seretti, Carlos Sepulveda, Sarah Dashun, Aliyauna NyKol, Debra Jackson, Ryan Houston, Jason Carmicheal.
Cinematographer, Kevin Keller ; editor, Lakisha R. Lemons ; music, Phillip Redmond.
In English; closed captioning available.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 15, 2021)
Keywords: African American men -- Religious life -- Drama; African American families -- Drama; Family -- Drama; Feature films; Fiction films; Internet videos; Streaming video